What is Driving Financial De-Dollarization in Latin America? - Garcia-Escribano, Mercedes (IMF Working Papers; Working Paper ;, 2011)
In the last decade, a group of Latin American countries (Bolivia, Paraguay, Peru, and Uruguay) experienced a gradual, yet sustained decline in financial dollarization. This paper documents the stylized facts and uses a standard VAR approach to examine the drivers of both deposit and credit de-dollarization. It finds that the exchange rate appreciation has been a key factor explaining deposit de-dollarization. The introduction of prudential measures to create incentives to internalize the risks of dollarization (including an active management of reserve requirement differentials), the development of a capital market in local currency, and de-dollarization of deposits have all contributed to a decline in credit dollarization. Continuing efforts on these fronts, while maintaining macroeconomic stability and strong fundamentals, would help deepening de-dollarization.